RELIGIOUS MODERATION AS A RESPONSE TO RADICALISM: INSIGHTS FROM THE QUR’AN, HADITH, AND THE PROPHET’S CHARACTER - Suparta, Mundzier; Hady, Yazid; Abusiri, Abusiri; Mubin, Fatkhul (Hikmah: Journal of Islamic Studies, 2025)
AbstractReligious radicalism in Indonesia deviates from Islam’s core values of justice, mercy, and balance, often manifesting in exclusivism, intolerance, and violence. This article explores the normative principles of religious moderation (wasathiyyah) as expressed in the Qur’an, Hadith, and the Prophet Muhammad’s exemplary character, analysing their relevance in countering contemporary radicalism. Using a qualitative method, it examines primary Islamic texts and secondary scholarship, identifying key themes through socio-historical interpretation and maqāṣid al-sharī‘ah. The findings show that moderation understood as a balanced middle path between excess (ifrāṭ) and negligence (tafrīṭ) is a central Islamic tenet, affirmed in Q.S. Al-Baqarah: 143 and Q.S. Al-Hujurat: 13. The Prophet embodied moderation through gentleness, openness, and respect for diversity, providing a model for balanced thought and practice. Moderation also applies to theology, worship, ethics, and law, shaping an inclusive, peace-oriented Islamic framework. Integrating these values into education, preaching, and policy is vital to counter radicalism, strengthen tolerance, and maintain Islam’s role as rahmatan lil-‘ālamīn. Moderation thus emerges as both a normative imperative and an effective strategy for harmony in pluralistic societies.AbstrakRadikalisme agama di Indonesia menyimpang dari nilai inti Islam, yaitu keadilan, kasih sayang, dan keseimbangan, yang sering termanifestasi dalam sikap eksklusif, intoleran, dan kekerasan. Artikel ini mengkaji prinsip normatif moderasi beragama (wasathiyyah) sebagaimana tercermin dalam Al-Qur’an, Hadis, dan teladan Nabi Muhammad SAW, serta relevansinya dalam menghadapi radikalisme kontemporer. Dengan metode kualitatif, penelitian ini menelaah teks-teks Islam primer dan literatur akademik sekunder, mengidentifikasi tema utama melalui interpretasi sosio-historis dengan pertimbangan maqāṣid al-sharī‘ah. Temuan menunjukkan bahwa moderasi—jalan tengah yang seimbang antara ifrāṭ (berlebihan) dan tafrīṭ (meremehkan)—merupakan ajaran utama Islam, ditegaskan dalam Q.S. Al-Baqarah: 143 dan Q.S. Al-Hujurat: 13. Nabi meneladani moderasi melalui kelembutan, keterbukaan, dan penghormatan terhadap keragaman, menjadi model bagi keseimbangan pemikiran dan praktik. Moderasi juga mencakup akidah, ibadah, etika, dan hukum, membentuk kerangka Islam yang inklusif dan damai. Integrasi nilai-nilai ini dalam pendidikan, dakwah, dan kebijakan publik penting untuk melawan radikalisme, memperkuat toleransi, dan menjaga Islam sebagai rahmatan lil-‘ālamīn. Moderasi terbukti sebagai keharusan normatif dan strategi efektif membangun harmoni dalam masyarakat plural.